2011
DOI: 10.1007/s13132-011-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Innovation and Differentiated Responses to Globalisation—A Case Study of Innovation Modes in the Agder Region, Norway

Abstract: The main argument of this paper is that firms and industries are dominated by different innovation modes and that they therefore respond differently to challenges of globalisation. The paper differentiates between three modes: science, technology and innovation (STI), doing, using and interacting (DUI) application mode and the DUI technological mode. These innovation modes are based on different dominant knowledge bases, modes of learning and external knowledge. What is the implication of these differences wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…They are also consistent with the essential conclusions drawn by Jensen et al (2007) from the empirical evidence in Denmark, Amara et al (2008) in Canada, Chen and Guo (2010) in China, Aslesen et al (2012) in Norway, Isaksen and Karlsen (2012a), Isaksen and Nilsson (2013) in Sweden, and Apanasovich (2014a) in Belarus. More specifically, the most successful firms are not those employing "pure" innovation modes, but rather those adopting innovation strategies that blend typical elements of the STI mode with the learning by doing, using and interacting practices characteristic of the DUI innovation mode.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…They are also consistent with the essential conclusions drawn by Jensen et al (2007) from the empirical evidence in Denmark, Amara et al (2008) in Canada, Chen and Guo (2010) in China, Aslesen et al (2012) in Norway, Isaksen and Karlsen (2012a), Isaksen and Nilsson (2013) in Sweden, and Apanasovich (2014a) in Belarus. More specifically, the most successful firms are not those employing "pure" innovation modes, but rather those adopting innovation strategies that blend typical elements of the STI mode with the learning by doing, using and interacting practices characteristic of the DUI innovation mode.…”
Section: Discussionsupporting
confidence: 87%
“…Amara et al, 2008;Marlon & Lambert, 2009;Ž ížalová, 2009;Guo et al, 2010;Isaksen & Karlsen, 2010Chen et al, 2011;Trippl, 2011;Aslesen et al, 2012;Gokhberg et al, 2012;Gonzalez-Pernia et al, 2012;Parrilli & Elola, 2012;Fitjar & Rodriguez-Pose, 2013;Isaksen & Nilsson, 2013;Apanasovich, 2014a;Gonzalez-Pernia et al, 2014).…”
Section: Introductionunclassified
“…Our hypothesis (1b) goes in line with some previous analyses on Denmark and Norway (Jensen et al, 2007;Aslesen et al, 2011), where the combined effect of STI and DUI types of collaboration is tested vis-à-vis the single effect of STI collaboration or DUI collaboration. Our conjecture is that the innovation output benefits from the combination in which the firm absorbs both scientific and experience-based knowledge inputs from both STI and DUI sorts of partners.…”
Section: Determinants Of Product and Process Innovationsupporting
confidence: 88%
“…Such ideal approach has been analyzed in various geographical contexts, such as China (Chen et al, 2011), Scandinavian countries (mainly Denmark and Norway; see Jensen et al, 2007;Aslesen et al, 2011;Fitjar and Rodríguez-Pose, 2013;Isaksen and Karlsen, 2010), and Spain (Parrilli and Elola, 2012). While some studies support that both STI and DUI contribute positively to innovation output, other studies present more nuanced outcomes (Chen et al, 2011;Parrilli and Elola, 2012;Fitjar and Rodríguez-Pose, 2013).…”
Section: Sti and Dui Learning Modesmentioning
confidence: 99%
“…However, their country-based analyses on the modes of innovation (derived from the literature on innovation systems, i.e. Lundvall, 1992;Cooke et al, 2004) have been mainly tested in market economies (Jensen, et al, 2007;Amara et al, 2008;Aslesen et al, 2012;Parrilli & Elola, 2012;Isaksen and Nilsson, 2013;Fitjar and Rodriguez-Pose, 2013;Malaver and Vargas, 2013;Nunes &Lopes, 2015;Parrilli & Alcalde, 2016). These studies have shown that firms that combine STI and DUI modes of learning are more likely to innovate than those relying on the STI and DUI mode taken separately.…”
Section: Introductionmentioning
confidence: 99%